2014
DOI: 10.5665/sleep.3494
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Loss, Circadian Mismatch, and Abnormalities in Reorienting of Attention in Night Workers with Shift Work Disorder

Abstract: Our results demonstrate specific deficits in neurophysiological activity in the attentional domain among the shift-work disorder group relative to night workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 69 publications
6
43
4
2
Order By: Relevance
“…In Assarrodi et al s' study, it was found that physical problems are less than mental health problems (29). Gumenyuk et al, in their study, concluded that workers with shift work disorder and night shift have specific deficits in neurophysiological activity in the attentional domain (30). Most of nurses working in shifts in the study of Majidi, reported the negative impact of shift work on their fatigue and health (31).…”
Section: Discussionmentioning
confidence: 99%
“…In Assarrodi et al s' study, it was found that physical problems are less than mental health problems (29). Gumenyuk et al, in their study, concluded that workers with shift work disorder and night shift have specific deficits in neurophysiological activity in the attentional domain (30). Most of nurses working in shifts in the study of Majidi, reported the negative impact of shift work on their fatigue and health (31).…”
Section: Discussionmentioning
confidence: 99%
“…For example, those with shift work disorder have shorter sleep duration, shorter sleep latency on the multiple sleep latency test, hyperreactivity to novel stimuli, and reduced brain response to auditory stimuli as measured by brain event-related potentials. [41][42][43] It has also been suggested that there are 2 distinct phenotypes within those with shift work disorder, namely, those with insomnia and sleepiness and those with only insomnia. Patients with both insomnia and sleepiness were found to be more likely to have a long tandem repeat on PER3 than those with insomnia but no sleepiness.…”
Section: Shift Work Disordermentioning
confidence: 97%
“…Vast differences in shift work schedules and duration of shift work may exist. Additionally, the degree of impairment during shift work likely reflects the degree of circadian desynchrony [46]. If individuals with impairment abandon shift work while individuals who tolerate non-traditional shifts remain in their current job, the healthy worker effect results [57,58].…”
Section: -163)mentioning
confidence: 99%